Role of M protein in adherence of group A streptococci. - Caparon, M G (1991)
The role of the M protein in adherence of group A streptococci to human epithelial cells was directly tested by using an isogenic pair of M+ and M- strains. There was no difference between these strains in the number of streptococcal units that adhered to buccal or tonsillar epithelial cells, indicating the following: (i) that adhesins that are not dependent upon M protein expression are present on the surface of group A streptococci and (ii) that the M protein is not the primary streptococcal adherence ligand. However, the M+ strain adhered to tonsillar epithelial cells as aggregates. This aggregation was dependent on the presence of the M protein, since the isogenic M- strain did not clump. The coaggregation of streptococci suggests that the M protein plays an important role in promoting the formation of microcolonies after initial attachment. Binding to fibronectin, a potential epithelial cell receptor for group A streptococci, was also the same for the isogenic M+ and M- strains as well as for an isogenic strain with a regulatory mutation that decreases the expression of M protein. In summary, the M protein is not the primary streptococcal adhesin, nor is it required to orient the streptococcal adhesin and/or fibronectin receptor.